2013
DOI: 10.1002/2013ja018734
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Pi2 pulsations by intermittent earthward propagating dipolarization fronts: An MHD case study

Abstract: [1] Using a global magnetohydrodynamic (MHD) simulation of the magnetosphere during a disturbed interval on 14 September 2004, we have investigated fluctuations in plasma properties of the magnetotail in the Pi2 range and their relationship to dipolarization fronts (DFs). Results from the MHD simulation indicate that this event is a very active interval with variable convection and disorder in the tail on a range of scales as small as 1 R E . DFs are observed in the simulation at the leading edge of fast earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Using a selection of 48 Pi2 events that occurred when Time History of Events and Macroscale Interactions during Substorms (THEMIS) was in the inner magnetosphere, Kwon et al [2012] has shown that space and ground observations of Pi2 are coherent if the satellite is within about 3 h of MLT of the ground station. Ream et al [2013] showed that the pulsations observed in the UCLA simulation are coherent for ∼2.5 h MLT at a radial distance of 6 R E , in good agreement with the observational results. The upper limit of the coherence in the LFM results is 2 h MLT.…”
Section: Simulation Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Using a selection of 48 Pi2 events that occurred when Time History of Events and Macroscale Interactions during Substorms (THEMIS) was in the inner magnetosphere, Kwon et al [2012] has shown that space and ground observations of Pi2 are coherent if the satellite is within about 3 h of MLT of the ground station. Ream et al [2013] showed that the pulsations observed in the UCLA simulation are coherent for ∼2.5 h MLT at a radial distance of 6 R E , in good agreement with the observational results. The upper limit of the coherence in the LFM results is 2 h MLT.…”
Section: Simulation Resultssupporting
confidence: 84%
“…The substorm selected for this case study occurred on 14 September 2004. Observations of this event have previously been presented by Cao et al [2008Cao et al [ , 2012 and Ream et al [2013] and are shown for the interval from 1700 to 1900 UT in Figure 1. The panels from top to bottom show the AL index [Davis and Sugiura, 1966] (Figure 1a), B H from the Urumqi magnetometer (northwest China; 43.80 ∘ latitude, 87.70 ∘ longitude) ( Figure 1b), B H filtered to Pi2 frequencies ( Figure 1c), and magnetic field observations from the Double Star (TC1) satellite located in the plasma sheet at (−10.2, −1.6, 1.2) R E GSM (Figure 1d).…”
Section: Observationsmentioning
confidence: 89%
See 3 more Smart Citations